The Role of Investment Interest in Linking Inflation, Exchange Rate, and Interest Rate Perceptions to Gold Investment Decisions - Ahmad Syawal Senong Pakata; Muh Fiqran; Sitti Fatima; Ahmad Nouruzzaman; M Ikhsan Purnama (Program Studi Perbankan Syariah, IAIN Palopo, 2025)
This study aims to analyze the effect of inflation perception, exchange rate, and interest rate on gold investment decisions with investment interest as a mediating variable. The study uses a quantitative approach with an explanatory design. Data were collected through a survey using a questionnaire administered to respondents who had experience or interest in gold investment using purposive sampling. Data analysis was performed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM). The results show that inflation perceptions have a positive and significant effect on investment interest, while exchange rates and interest rates do not have a significant effect on investment interest. In addition, these three macroeconomic variables do not have a significant direct effect on gold investment decisions. Conversely, investment interest has a positive and significant effect on gold investment decisions. The mediation analysis results show that investment interest fully mediates the relationship between inflation perception and gold investment decisions. These findings indicate that psychological factors play an important role in explaining individual investment behavior.